4 3 2 1, The Book of Endlessly Forking Paths - Ilana Shiloh (Revue LISA)
4 3 2 1, Paul Auster’s 2017 novel, is a creative exploration of counterfactual thinking – thinking about what might have been. 4 3 2 1 departs from the premise that “the real […] also consist[s] of what could have happened but didn’t”. This premise dictates Auster’s narrative strategy, which involves the juxtaposition of four alternative versions of the protagonist’s character and life. The novel’s structural principle evokes Borges’ iconic story, “The Garden of Forking Paths”, where the Argentinian author toys with the idea of bifurcating time and parallel fictional lives. In the vein of this Borgesian conceit, the time-line of Auster’s novel is also split into forking paths, deploying four different destinies of four protagonists by the same name, one of whom eventually turns out to be the author of the other three. If counterfactuals are conveyed through the imaginative creation of alternative realities, all fiction may be considered counterfactual. But Auster’s latest novel is still unique. Ever since Aristotle, fiction has aspired to mimesis, to a recognizable representation of reality. By broadening the concept of reality, Auster has created a new kind of mimesis, which blends the representation of the actual with that of the potential. The present paper offers a reading of 4 3 2 1 from the perspective of counterfactual thinking and examines its characteristics and cognitive value.